Pengaruh return on asset, debt to equity ratio, dan earning per share terhadap harga saham pada sektor consumer goods industry di bursa efek indonesia periode 2015 sampai 2019 - Josua Nobertho Marpaung; Cicilia Febiola; Senjoni Arjuna Sitanggang; Jamaluddin Jamaluddin (Jurnal Paradigma Ekonomika, 2021)
This study aims to analyze the effect of return on assets, debt to equity, and earnings per share on stock prices in the customer industry sector. Financial statement information is taken from companies' annual financial statements listed on the Indonesia Stock Exchange. The sampling method was taken from the purpose of sampling. The analysis tool uses multiple linear regression models. The study results found: (1) Return on assets and earnings per share have a significant effect on stock prices. (2) Debt to equity ratio has no significant effect on stock prices (3) Return on assets, debt on equity ratio, earnings per share simultaneously affect stock prices. The fundamental factors of return on assets, equity debt, and earnings per share can influence stock prices by 85.3%, while other factors influence 14.7%.